The generals : Patton, MacArthur, Marshall, and the winning of World War II - Groom, Winston, 1944-2020- (National Geographic, 2015)
Groom tells the intertwined and uniquely American tales of George Patton, Douglas MacArthur, and George Marshall. These three remarkable men-of-arms who rose from the gruesome hell of the First World War to become the finest generals of their generation during World War II redefined America's ideas of military leadership and brought forth a new generation of American soldier. Against the backdrop of the most dramatic moments of the twentieth century, you'll discover new insights into the lives of America's most celebrated warriors.